Characteristics of bio-composites from Polyvinyl alcohol reinforced micro-cellulose fibers of Paederia foetida - Nasmi Herlina Sari; Muhammad Nabil Fadhlurrohman Rivlan; Suteja Suteja; Syarif Hidayatullah; I Putu Lokantara (Green Engineering Society, 2026)
The use of renewable natural fibers as reinforcements in biodegradable matrices has been boosted by the development of sustainable polymer materials. The purpose of this work is to examine the properties of bio-composites made of polyvinyl alcohol (PVA) reinforced with micro-cellulose fibers that are isolated from the underused plant resource Paederia foetida (MSPf). After retting and alkaline and bleaching treatments, micro-cellulose was obtained and added to PVA at a weight percentage of 5% utilizing the solution casting technique. The biocomposites' mechanical, thermal, water absorption, and morphological characteristics were assessed. When MSPf was added, PVA's tensile strength rose from 20.69 MPa to 23.10 MPa, and its elastic modulus increased dramatically, suggesting better stiffness and efficient stress transfer. The improvement is ascribed to the hydroxyl groups of PVA and cellulose having strong hydrogen bonds and good interfacial adhesion. Due to limited polymer chain mobility, elongation at break decreased, but the composite showed better structural integrity. After 36 h, water absorption attained an equilibrium value of 1.461%, indicating the creation of a compact fiber-matrix network. When compared to clean PVA, thermogravimetric analysis showed better thermal stability, and SEM verified strong interfacial compatibility and homogeneous dispersion. These results show that micro-cellulose derived from Paederia foetida is a viable sustainable reinforcement that can improve the performance of bio-composites based on PVA.